2017
DOI: 10.2527/tas2016.0006
|View full text |Cite
|
Sign up to set email alerts
|

High milk production decreases cow-calf productivity within a highly available feed resource environment

Abstract: The beef cattle industry tends to focus on selecting production traits with the purpose of maximizing cow-calf performance. One such trait is milking ability, which is considered the primary influence on weaning weight of the calf. Therefore, the objective of this study was to determine the effect of actual milk yield on reproductive performance, circulating blood metabolites, and calf performance in beef cows in the Southeastern US. Over a 2 yr period, data were collected from 237, 3- to 9-yr-old Angus-sired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Similarly, Pushpakumara et al (2003) noted no differences in 24-h milk yield between dairy cows that were diagnosed as pregnant by early or late service. However, Edwards et al (2017) reported a decreased TAI pregnancy rate in high milk producing multiparous beef cows compared with low and moderate milk producing multiparous beef cows.…”
Section: Resultsmentioning
confidence: 89%
“…Similarly, Pushpakumara et al (2003) noted no differences in 24-h milk yield between dairy cows that were diagnosed as pregnant by early or late service. However, Edwards et al (2017) reported a decreased TAI pregnancy rate in high milk producing multiparous beef cows compared with low and moderate milk producing multiparous beef cows.…”
Section: Resultsmentioning
confidence: 89%
“…In this study, abundant native tallgrass prairie forage was available to those cows throughout the growing season but daughters of high milk EPD sires actually produced less milk than daughters of moderate EPD sires. Edwards et al, (2017) found that increased milk yield of beef cows resulted in no improvement in calf weaning BW. Their work suggested that selection for greater milk yield in their environment did not improve cow/calf enterprise income, although it may increase expenses and reduce the effective stocking rate.…”
Section: Discussionmentioning
confidence: 98%
“…A large challenge for the cowherd, especially in limited resource environments, is an increase in selection for greater milk production. An increase in selection for milk production has resulted in beef cows under greater nutritional stress during early lactation, which ultimately reduces overall reproduction and cowherd efficiency (Edwards et al, 2017). These authors determined the impact of milk production on cow/ calf performance in Angus and Angus crossbred cows with milk ranging from 6.5 to 12 kg/d at peak milk production.…”
Section: Genetic Selection To Increase Metabolic Efficiencymentioning
confidence: 99%
“…Even when forage or forage quality is abundant, the production cycle in cattle is energetically demanding due to the energetic costs of lactation and gestation. Energetic costs of lactation are even more exacerbated if genetic potential exceeds the environmental capacity (Edwards et al, 2017). Furthermore, the ability to adapt and cope with the nutritional challenges varies greatly among livestock, in which genetic potential and metabolic imprinting is likely an explanation (Gross and Bruckmaier, 2015).…”
Section: Introductionmentioning
confidence: 99%